Estimating step parameters using photoelectric cells - Healy, R.; Kenny, I. C.; Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to assess the OptoJumpTM photocell system (Microgate, Bolzano, Italy) in measuring step length and ground contact time during running. In two separate investigations, eight individuals repeatedly ran through a three metre section of OptoJumpTM track. Ground contact times were compared to concurrent force platform measures whereas step lengths were compared to physically measured lengths from foot imprints left in powder. Estimates of step length showed excellent validity with only 0.4% difference between methods and an intraclass correlation coefficient of 0.999. The OptoJumpTM systematically overestimated contact time with a mean bias of 2.7% compared to force platform measures. These results suggest that the OptoJumpTM can be effectively used to estimate step characteristics in real time.